Single-feed circularly polarized equilateral-triangular microstrip antenna with a tuning stub. - Jui-Han Lu (IEEE Transactions on antennas and propagation)
Novel circular polarization (CP) designs of single-feed equilateral-triangular microstrip antennas are proposed and experimentally studied. The proposed CP designs can easily be achieved by loading a narrow tuning stub at the triangle tip or at the center of the bottom edge of the triangular patch. Moreover, by embedding a cross-slot of equal slot lengths in the triangular patch, a compact CP operation can easily be obtained, with an antenna size reduction up to about 22%, as compared to the CP design of a regular triangular microstrip antenna without cross-slot at a fixed frequency